Ù…ÙˆØ§Ù‚Ù Ø§Ø¨Ù† Ù‚Ø¯Ø§Ù…Ø© ØªØ¬Ø§Ù‡ Ø¢Ø±Ø§Ø¡ Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø§Ù„Ø£ØµÙˆÙ„ÙŠØ© Ù…Ù† Ø®Ù„Ø§Ù„ ÙƒØªØ§Ø¨ Ø±ÙˆØ¶Ø© Ø§Ù„Ù†Ø§Ø¸Ø± ÙˆØ¬Ù†Ø© Ø§Ù„Ù…Ù†Ø§Ø¸Ø± - Basri, Muhammad Muinudinillah; Apriantoro, Muhamad Subhi (Profetika: Jurnal Studi Islam, 2017)
This publication discusses the thought of ushul fiqh Muâ€™tazilah in the book of Raudhot an-Nadzir wa Jannat al-Manadzir written by Ibnu Qudamah. The book is the summary of Al Mustashfa written by Imam Al Ghozali. Al Mustasfha contains diction which is not easily understood. It relates with the method used by Imam Al Ghazali namely method of Al-Mutakallimin. Therefore, book of Raudhot an-Nadzir wa Jannat al-Manadzir discusses the thought of ushul fiqh Muâ€™tazilah. The method of the research was qualitative method. It can be identified that Ibnu Qudamah adopts the thought of Al Ghozali without putting down his name in his book. In this book, Ibnu Qudamah sometimes has the same and different opinion with Al Ghozali. However, they also have same thought with different sampling cases. The thought of ushul fiqh Muâ€™tazilah influences the method of contemporary ushul fiqh. One of the influences is a human freedom to do ijtihad with the right to create their own fate. There is also a difference between old and new Muâ€™tazilah.Â  In the old perspective, the law consideration is about God (theocentric). Meanwhile, in the new perspective, the law consideration is about human (anthropocentric) ÙŠØ¨ØØ« ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ù†Ø´Ø±Ø© Ø¹Ù† Ø¢Ø±Ø§Ø¡ Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø§Ù„Ø£ØµÙˆÙ„ÙŠØ© Ø§Ù„ØªÙŠ Ø£ÙˆØ±Ø¯ØªÙ‡Ø§ Ø§Ø¨Ù† Ù‚Ø¯Ø§Ù…Ø© Ø®Ù„Ø§Ù„ ÙƒØªØ§Ø¨Ù‡ Ø±ÙˆØ¶Ø© Ø§Ù„Ù†Ø§Ø¸Ø± ÙˆØ¬Ù†Ø© Ø§Ù„Ù…Ù†Ø§Ø¸Ø± Ù„Ù…Ø§ ÙƒØ§Ù† Ù‡Ø°Ø§ Ø§Ù„ÙƒØªØ§Ø¨ Ù…Ø®ØªØµØ±Ø§ Ù…Ù† ÙƒØªØ§Ø¨ Ø§Ù„Ù…Ø³ØªØµÙÙ‰ ÙÙŠ Ø¹Ù„Ù… Ø§Ù„Ø£ØµÙˆÙ„ Ù„Ø£Ø¨ÙŠ ØØ§Ù…Ø¯ Ø§Ù„ØºØ²Ø§Ù„ÙŠ ÙÙ‚Ø¯ Ø¹Ø±Ø¶ ÙƒØ«ÙŠØ± Ù…Ù† Ø¹Ø¨Ø§Ø±ØªÙ‡ Ø¨ØºÙ…ÙˆØ¶ ÙˆØ¥Ø¨Ù‡Ø§Ù…. Ù‡Ø°Ø§ Ù„Ø§ ÙŠØ®Ø±Ø¬ Ø¹Ù† ÙƒÙˆÙ† Ø§Ù„ØºØ²Ø§Ù„ÙŠ Ù†Ù‡Ø¬ Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù…ØªÙƒÙ„Ù…ÙŠÙ† ÙÙŠ ÙƒØªØ§Ø¨Ø© Ø§Ù„Ù…Ø³ØªØµÙÙ‰. Ù„Ù‡Ø°Ø§ Ù‚Ø¯ ØªÙ…ÙŠØ² Ø±ÙˆØ¶Ø© Ø§Ù„Ù†Ø§Ø¸Ø± Ø¨Ø¢Ø±Ø§Ø¡ Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø§Ù„Ø£ØµÙˆÙ„ÙŠØ©. Ø³Ù„Ùƒ Ø§Ù„Ø¨Ø§ØØ« Ù…Ù†Ù‡Ø¬ ÙƒÙŠÙÙŠ ØªØ¨ÙŠÙ† Ù…Ù† Ø§Ù„Ø¨ØØ« Ø£Ù† Ø§Ø¨Ù† Ù‚Ø¯Ø§Ù…Ø© Ù…Ù‡Ù…Ø§ ÙƒØ§Ù† Ø£Ø®Ø° ÙƒØ«ÙŠØ± Ù…Ù† Ø¢Ø±Ø§Ø¡ Ø§Ù„ØºØ²Ø§Ù„ÙŠ ÙÙŠ ÙƒØªØ§Ø¨Ù‡ØŒ ÙˆÙ‡Ùˆ Ù„Ù… ÙŠØ°ÙƒØ± Ø§Ø³Ù… Ø§Ù„ØºØ²Ø§Ù„ÙŠ Ù‚Ø· Ø®Ù„Ø§Ù„ ÙƒØªØ§Ø¨Ù‡ØŒ ÙˆØ§ÙÙ‚ Ø§Ù„ØºØ²Ø§Ù„ÙŠ ØªØ§Ø±Ø© ÙˆØ®Ø§Ù„ÙÙ‡ ØªØ§Ø±Ø©ØŒ Ø£Ùˆ ÙˆØ§ÙÙ‚Ù‡ ÙÙŠ Ø§Ù„Ù…Ø¹Ù†Ù‰ ÙˆØ®Ø§Ù„ÙÙ‡ ÙÙŠ Ø§Ù„Ø£Ù…Ø«Ù„Ø©. ÙˆØ¢Ø±Ø§Ø¡ Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø§Ù„Ø£ØµÙˆÙ„ÙŠØ© Ù„Ù‡Ø§ ØªØ£Ø«ÙŠØ± ÙƒØ¨ÙŠØ± ÙÙŠ Ù…Ù†Ø§Ù‡Ø¬ Ø§Ù„Ø£ØµÙˆÙ„ÙŠØ© Ø§Ù„Ù…Ø¹Ø§ØµØ±Ø©ØŒ Ù…Ù†Ù‡Ø§ Ø£Ù† Ø¨Ø§Ø¨ Ø§Ù„Ø§Ø¬ØªÙ‡Ø§Ø¯ ÙØªØ Ø¨Ø´ÙƒÙ„ ÙˆØ§Ø³Ø¹ Ù„Ù„ØØ±ÙŠØ© Ø§Ù„Ø£ÙØ¹Ø§Ù„ Ø§Ù„Ø¥Ù†Ø³Ø§Ù†ÙŠØ©ØŒ ÙˆØ¬ÙˆØ¯ Ø§Ù„ÙØ±ÙˆÙ‚ Ø¨ÙŠÙ† Ù…Ø¨Ù†Ù‰ Ø§Ù„ÙÙƒØ±Ø© Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø§Ù„Ù‚Ø¯Ù…Ø§Ø¡ Ø¨Ù…Ù† ÙŠØ¯Ø¹Ù‰ Ø£Ù†Ù‡ Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø¨Ø«ÙˆØ¨Ù‡Ø§ Ø§Ù„Ø¬Ø¯ÙŠØ¯. Ø£Ù† Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø§Ù„Ù‚Ø¯Ù…Ø§Ø¡ ÙŠØ¬Ø¹Ù„ÙˆÙ† Ø§Ù„Ø¥Ù„Ù‡ Ù…ØÙˆØ± ÙƒÙ„ Ø´ÙŠØ¡ØŒ Ø£Ù…Ø§ Ø§Ù„Ù…Ø¹ØªØ²Ù„Ø© Ø§Ù„Ù…Ø¹Ø§ØµØ±Ø© ÙØ¥Ù†Ù‡Ù… Ø¬Ø¹Ù„ÙˆØ§ Ø§Ù„Ø¥Ù†Ø³Ø§Ù† Ù…ØÙˆØ± ÙƒÙ„ Ø´ÙŠØ¡.